THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY AND GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE - Novita Sari; Nova Diana; Rahmadianti; Putri Elisa (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study aims to determine the influence of Corporate Social Responsibility and Good Corporate Governance on financial performance in manufacturing sector companies on the Indonesia Stock Exchange. The method used in this study is quantitative research method with multiple linear regression equation model. The results of the study show that Corporate Social Responsibility has a t-count of 2.538415 with coefficient value The regression of the Corporate Social Responsibility variable (X1) is 0.179732. The significance value of Corporate Social Responsibility is 0.0247 which means that Corporate Social Responsibility shows a positive and significant influence on Financial Performance. Good Corporate Governance (X2) obtained a t-count of 2.782864. The significance value is 0.0405 which means > α = 0.05 (5%). This shows that Good Corporate Governance (X2) has a significant influence on Financial Performance manufacturing sector for the 2018-2022 period. The test results show that there is a simultaneous influence between Corporate Social Responsibility and Good Corporate Governance on Financial Performance. Based on the results of the F-test, namely 34.28565 using a significance level of 95%, a = 5%. The significance value (sig) is 0.002798 or < α = 5% (0.05) which means that there is a significant influence of the independent variables, namely Corporate Social Responsibility and Good Corporate Governance, together or simultaneously on the dependent variable, namely the Financial Performance of the manufacturing sector listed on the Indonesia Stock Exchange for the 2018-2022 period